2021
DOI: 10.1038/s41418-021-00892-y
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity-associated glutamine deficiency is a predisposition to severe COVID-19

Abstract: SARS-CoV-2 vaccinations have greatly reduced COVID-19 cases, but we must continue to develop our understanding of the nature of the disease and its effects on human immunity. Previously, we suggested that a dysregulated STAT3 pathway following SARS-Co-2 infection ultimately leads to PAI-1 activation and cascades of pathologies. The major COVID-19-associated metabolic risks (old age, hypertension, cardiovascular diseases, diabetes, and obesity) share high PAI-1 levels and could predispose certain groups to seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 191 publications
(205 reference statements)
2
41
0
Order By: Relevance
“…Ct values of RT-PCR in the patients with comorbidities were lower [ 86 ]. Hypertension, cardiovascular diseases, diabetes, and obesity related to abnormal immune response [ 117 ]. The outcomes of COVID-19 are primarily influenced by comorbidities and particular disease states or treatments in patients with rheumatic diseases [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ct values of RT-PCR in the patients with comorbidities were lower [ 86 ]. Hypertension, cardiovascular diseases, diabetes, and obesity related to abnormal immune response [ 117 ]. The outcomes of COVID-19 are primarily influenced by comorbidities and particular disease states or treatments in patients with rheumatic diseases [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of glutamine as an adjuvant in the treatment of COVID-19 patients showed a putative synergistic effect on immune defense [ 37 ]. Glutamine deficiency and increased hyaluran in the lungs have emerged as central metabolic characteristics that prompt COVID-19 patients to severe pathophysiology [ 38 ]. Metabolomic studies have also shown a reduced glutamine/glutamate ratio in COVID-19 patients, indicating a metabolic rewiring of energy metabolism and systematic implications during infection that could be clinically valuable [ 17 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine is also one of the three amino acids needed for glutathione (GSH) synthesis. GSH, a tripeptide formed by glutamate, glycine and cysteine, represents the most important body endogenous antioxidant system, being active mainly in the cell mitochondria and nucleus (102,103). Intracellular glutamine as glutamate precursor is fundamental for the synthesis of GSH (99).…”
Section: Muscle Oxidative Stressmentioning
confidence: 99%